Highly Fluorescent Nitrogen-Doped Graphene Quantum Dots’ Synthesis and Their Applications as Fe(III) Ions Sensor - Fei Lu; Yi-hua Zhou; Li-hui Wu; Jun Qian; Sheng Cao; Ya-feng Deng; Yuan Chen (International Journal of Optics)
Nitrogen-doped graphene quantum dots (N-GQDs) with strong blue fluorescence and a high quantum yield of 88.9% were synthesized via a facile one-pot hydrothermal treatment with citric acid (CA) and ethylenediamine (EDA) as carbon and nitrogen sources, respectively. The blue fluorescence emission is independent of the excitation wavelengths. These N-GQDs dispersed well in water and ethyl alcohol and showed a highly selective and sensitive detection of hazardous and toxic Fe3+ in the range of 1600μmol/L to 6000μmol/L through a fluorescence quenching process with a detection limit of 2.37μmol/L. Based on the excellent sensitivity and selectivity of N-GQDs to heavy metal ions, paper-based sensors can be fabricated by inkjet printing, which are rapid but low cost. So the visual instant on-site identification of heavy metal ion will be realized in the future.